Response of Degarelix treatment in human prostate cancer monitored by HR-MAS (1)H NMR spectroscopy - Madhu, Basetti (Metabolomics, 2016)
INTRODUCTION: The androgen receptor (AR) is the master regulator of prostate cancer cell metabolism. Degarelix is a novel gonadotrophin-releasing hormone blocker, used to decrease serum androgen levels in order to treat advanced human prostate cancer. Little is known of the rapid metabolic response of the human prostate cancer tissue samples to the decreased androgen levels. OBJECTIVES: To investigate the metabolic responses in benign and cancerous tissue samples from patients after treatment with Degarelix by using HRMAS (1)H NMR spectroscopy. METHODS: Using non-destructive HR-MAS (1)H NMR spectroscopy we analysed the metabolic changes induced by decreased AR signalling in human prostate cancer tissue samples. Absolute concentrations of the metabolites alanine, lactate, glutamine, glutamate, citrate, choline compounds [t-choline = choline + phosphocholine (PC) + glycerophosphocholine (GPC)], creatine compounds [t-creatine = creatine (Cr) + phosphocreatine (PCr)], taurine, myo-inositol and polyamines were measured in benign prostate tissue samples (n = 10), in prostate cancer specimens from untreated patients (n = 7) and prostate cancer specimens from patients treated with Degarelix (n = 6). RESULTS: Lactate, alanine and t-choline concentrations were significantly elevated in high-grade prostate cancer samples when compared to benign samples in untreated patients. Decreased androgen levels resulted in significant decreases of lactate and t-choline concentrations in human prostate cancer biopsies. CONCLUSIONS: The reduced concentrations of lactate and t-choline metabolites due to Degarelix could in principle be monitored by in vivo (1)H MRS, which suggests that it would be possible to monitor the effects of physical or chemical castration in patients by that non-invasive method. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11306-016-1055-0) contains supplementary material, which is available to authorized users.